Specyfika nauczania archeologii śródziemnomorskiej na Uniwersytecie im. Adama Mickiewicza w Poznaniu w kontekście tematów podejmowanych w pracach dyplomowych - Hordecki, Jędrzej; Filipowicz, Patrycja (Folia Praehistorica Posnaniensia, 2024)
The article explores the specificities of teaching Mediterranean archaeology at Adam Mickiewicz University in Poznań, within the context of the Oriental and Ancient Archaeology specialization. Using a comprehensive analysis of 258 diploma theses defended between 2004 and 2024, it identifies dominant research trends, thematic interests, and their alignment with the faculty’s academic programs and research priorities. The findings reveal a gradual broadening of the discipline’s scope to include prehistoric and ancient studies of the Mediterranean and neighboring regions. This trend mirrors shifts in student interests and academic discourse on integrating traditional and modern archaeological methodologies. The study provides a reflective evaluation of the specialization’s contribution to Polish academic traditions and its potential future directions.